In this blog entry we will look at two equations and see if there are solutions to them.
Things to Know:
In the realm of complex numbers, i = √(-1).
For the function f(x) = ln x:
If x > 0 and x is real, then ln x is also real and ln x = ln x.
If x < 0 and x is real, then ln x is complex and ln x = ln |x| + i * π.
If x is a complex number, such that x = a + bi, then:
ln x = ln r + i * θ where:
r = √(a^2 + b^2)
θ = atan(b/a) where -π ≤ θ ≤ π
Laws of Logarithm Needed:
Where a and b are any numbers:
ln (a^b) = b * ln a
ln(a * b) = ln a + ln b
ln(a / b) = ln a - ln b
And (a + b*i)^n = r^n * e^(i * π * θ) = r^n * (cos(n*θ) + i * sin(n*θ))
A^x = 0
(I) A^x = 0
Start by taking the logarithm of both sides:
(II) ln (A^x) = ln 0
(III) x * ln A = ln 0
(IV) x = ln 0/ln A
Immediately we see a problem. The expression ln 0 is undefined. The function ln x approaches negative infinity when x approaches zero from the right side (that is x > 0 and calculating ln x as x is decreasing).
However, when x approaches from the left side, ln x approaches -infinity + i * π. There is no complex number makes the statement A^x = 0 true.
Therefore, A^x has no solutions. There is no x that makes statement (IV) in this section true.
A^x + B^x = 0
Let's see if we can get a closed form solution for x.
(I) A^x + B^x = 0
Assume that B can be rewritten as B = A^n., where n is any power. Then:
(II) A^x + (A^n)^x = 0
(III) A^x + (A^x)^n = 0
Factoring out A^x:
(IV) A^x * (1 + (A^x)^(n-1) ) = 0
From (IV) either:
A^x = 0, which can not happen sense from the previous section, A^x has no roots, real or complex.
So we have to look at the other possibility: (1 + (A^x)^(n-1) ) = 0.
(V) (A^x)^(n-1) = -1
(VI) A^x = -1^(1/(n-1))
The polar representation for -1 + 0i is 1*e^(i*π), a general solution for (VI) is:
(VII) A^x = cos((n-1) * π)+ i * sin((n-1)*π)
If n is an integer, then the roots of -1 can be found by the formula:
(-1)^(1/n) = cos((2*k+1)*π/n) + i*sin((2*k+1)*π/n) for k
(Source: Zwillinger, Daniel. CRC Standard Mathematical Tables and Formulae, 32nd Edition. CRC Press, 2012)
From (VII) of this section, let α = cos((n-1) * π) and β = sin((n-1)*π) and
(VIII) A^x = α + i * β
(IX) ln A^x = ln (α + i * β)
(x) x * ln A = ln(α + i * β)
Hence, a general solution to A^x + B^x = 0 where B = A^n is:
(XI) x = ln(α + i * β)/ln A
Where α = cos((n-1) * π) and β = sin((n-1)*π)
There are no real solutions to A^x + B^x = 0, only complex ones.
2^x + 8^x = 0
Since 8 = 2^3,
2^x + (2^3)^x = 0
2^x + (2^x)^3 = 0
2^x * (1 + (2^x)^2) = 0
There is no solution for 2^x = 0, so we look to (1 + (2^x)^2) = 0.
(1 + (2^x)^2) = 0
(2^x)^2 = -1
The square roots of -1 are i and -i.
One solution is:
2^x = i
x * ln 2 = ln i
x = ln i / ln 2 ≈ 2.266180071i
The other is:
2^x = -i
x * ln 2 = ln -i
x = ln -i / ln 2 ≈ -2.266180071i
And that is a way to find the roots of A^x + B^x = 0.
Until next time, Eddie
This blog is property of Edward Shore. 2013
Friday, July 19, 2013
Do A^x = 0 and A^x + B^x = 0 have roots?
Fun with the Radio Shack EC-4026 (Equivalent of the Casio fx-4500P) Programming Notes The syntax for prompting ...
Casio fx-991EX Classwiz Review Casio FX-991EX The next incarnation of the fx-991 line of Casio calculators is the fx-991 EX. ...
One of the missing features of the TI-82/83/84 family is the ability to convert between bases. Here are two programs in TI-Basic to help...
HP Prime: Basic CAS Commands for Polynomials and Rational Expressions Define the following variables: poly: a polynomial o...